Evaluating the education quality in the College of Fine Arts "Design Department as a model" (Al-Academy, 2022)
Education quality evaluation is one of the objectives of education quality. The evaluation includes assessing the education standards and academic program outcomes to develop intellectual, scientific and practical concepts for the educational structure. It considers the determination of the rates of the number of accepted students and graduates. The research focuses on "what are the levels of education quality according to the evaluation mechanisms in the design department" to enhance the quality system and the objectives of theoretical and applied education.It is identifying the levels of education quality and evaluating it according to the numbers and rates of graduate students of the design department branches for morning and evening studies from 2003 to 2021. This represents the research community and its sample. Using the stratified approach and analyzing data and information in a sequential or orderly manner to reach the most important conclusions:1-The levels of student admission numbers are unbalanced and unstable during the admission years, which affects the level of education and quality2- The graduation rates ranged between 60% and 70%, which was the highest. The average GPA is 80% was almost a fixed percentage relative to the number of students in the three groups, which indicates cognitive support and a practical orientation that came with the standards of quality and learning